Designing Rice Dryer with A Capacity Of 1000 Kg / Hour Using Rice Husk Heater - Agung Sutrisno (President University, 2021)
One way of processing agricultural products is by drying process. It is a process of reducing water content to a certain extent so that it can inhibit the rate of damage to agricultural products (rice) due to biological and chemical activities. Drying is the last step in a series of operations, and the drying product is usually ready to use. The goal of this research is to design Paddy Drier with 1000 Kg capacity. The result of the study showing the design specification of the drier